THE STRICTNESS OF TRADITIONAL INDICATORS FOR CREDITWORTHINESS MEASURING - Kuběnka, Michal (Vysoká škola ekonomická v Praze, 2016)
Creditworthy indicators are used as a tool for a rapid diagnosis of the financial health of a company. The classic models are the Q-test, the Credibility index and Rudolf Doucha´s Balance analysis, all of which were created decades ago. Despite this, they are still popular. These three indicators are among the most frequently used in scientific publications. The author asked a number of questions related to their practical use. Despite their age they have not yet been answered. For instance, do they still serve the purpose for which they were created? Does the assessment of financial health return the same results using these various indicators? Can individual indicators bring contradictory results describing the financial health of analyzed companies? Which is the best indicator describing companies´ economic condition? To answer these questions a set of nearly 1500 companies was analyzed. A key research finding is that the Credibility Index is the most accurate model for predicting creditworthiness and the accuracy of individual models varies. The results of the Q-test and the Balance Analysis I. using the Credibility Index can be very accurately predicted only on the basis of conditioned probability.
Přísnost tradičních indikátorů pro měření bonity
Keywords: financial health; indicators, Q-test; Credibility Index; Balance analysis; finanční zdraví; indikátory; Q-test; Index bonity; Bilanční analýza